Summable spaces and their duals, matrix transformations and geometric properties - Başar, Feyzi; Dutta, Hemen, 1981- (Boca Raton, FL : CRC Press, 2020)
The aim of Summable Spaces and Their Duals, Matrix Transformations and Geometric Properties is to discuss primarily about different kinds of summable spaces, compute their duals and then characterize several matrix classes transforming one summable space into other. The book also discusses several geometric properties of summable spaces, as well as dealing with the construction of summable spaces using Orlicz functions, and explores several structural properties of such spaces. Each chapter contains a conclusion section highlighting the importance of results, and points the reader in the direction of possible new ideas for further study. Features Suitable for graduate schools, graduate students, researchers and faculty, and could be used as a key text for special Analysis seminars Investigates different types of summable spaces and computes their duals Characterizes several matrix classes transforming one summable space into other Discusses several geometric properties of summable spaces Examines several possible generalizations of Orlicz sequence spaces
OCLC-licensed vendor bibliographic record.
Keywords: Summability theory; MATHEMATICS / General; MATHEMATICS / Applied; MATHEMATICS / Geometry / General